Indirect costs of bronchial asthma and its complications - Żaneta Kieliszek (Journal of Education, Health and Sport, 2019)
The study presents an analysis of indirect costs in Poland generated by bronchial asthma, which according to the ICD-10 classification was marked with number J45. The final indirect cost of absenteeism for asthma and asthmatic condition in 2016 amounted to PLN 236 513 435.66. The final cost of presenteeism is amounting to PLN 25 866 185,10. The final indirect cost of informal care in the amount of PLN 10 441 395.82 was obtained. The total amount of indirect costs of permanent or temporary inability to work due to asthma was obtained and it was PLN 588 322 336.36. The final indirect cost of deaths in the amount of PLN 48 609 887.82 was obtained.